(untitled) (Journal of Student Affairs in Africa, 2021)
Universities and colleges of education all over the world are experiencing student populations who bring diverse values and experiences into the learning environment. Student affairs professionals are faced with the challenge of accommodating each student’s unique needs. This paper intends to address the essentiality of multicultural competence in student affairs administration in higher education. It discusses the meaning of multiculturalism; the role of the student affairs in the development of the students; and the importance of multicultural competence in student affairs administration.